Correcting density/sonic logs for total organic carbon to reduce uncertainty in pore pressure prediction. (27th May 2020) - Green, Sam; Vernik, Lev
ABSTRACT: Pore pressure prediction in shales undergoing compaction, including both mechanical and chemical processes, is customarily related to the mechanism referred to disequilibrium compaction. However, even when this mechanism is established and the normal compaction trend in sonic velocity, as a proxy for shale porosity, is well constrained, the pore pressure prediction may be in error because of the lithological variation in shale composition. The presence of solid organic matter in excess amounts in shale formations that have never been exposed to the pressure–temperature conditions in the oil window is an example of these lithological effects, causing marked overprediction of pore pressure even in thermally immature mudrocks. This necessitates implementation of bulk density and sonic velocity log corrections in organic‐rich shales prior to performing standard pore pressure prediction workflows. In this paper, it is shown how these corrections can be made and the outcomes of the pore pressure prediction can be dramatically improved by using combination of rock physics models relating bulk density to total organic carbon and P‐wave velocity to bulk density in organic‐rich and conventional shales, respectively. To illustrate the workflow, a case study from a well drilled through the Kimmeridge Clay Formation in the North Sea, a well‐recognized source rock with total organic carbon content in the 2%–12% range and significant variation in clay content from 25% to 60%, both of which strongly affect the most commonly utilized log responses recorded in this formation. Using this old but data‐rich well, the importance of accounting for both total organic carbon and clay content variations in pore pressure prediction is demonstrated. It is also recognized that this workflow does not immediately apply to unconventional shale plays, where the pore pressure generation mechanisms are more complex and cannot be solely ascribed to compaction disequilibrium.